Impact of gated and guarded communities (GACOS) towards the social segregation influenced by the community: case study Kuala Terengganu, Terengganu / Muhammad Aizat Kamarudin - Kamarudin, Muhammad Aizat (2023)
This research aimed to determine the impact of GACOS housing toward community and analyse the solution to the impact. in Kuala Terengganu as the case study. The study adopted descriptive research designs, which involved questionnaire survey to community nearby the GACOS housing area. Quantitative data collected was analysed using descriptive analysis to identify the community perception towards the GACOS housing and the solution of the impact. Findings from this research shows GACOS housing give a lot of impact towards community and surrounding area such as towards social gap and individualistic. As this research found that the highest mean for solution of this impact is to do the community service or activities that bridge the gap between gated communities and the surrounding area. It followed by implementing the policies that require gated communities to contribute to public spaces or amenities accessible to non-residents in the 2nd rank and establishing community organizations that facilitate interaction between residents and nonresidents at the 3rd.